2006
DOI: 10.1080/17470210500314729
|View full text |Cite
|
Sign up to set email alerts
|

When do auditory/visual differences in duration judgements occur?

Abstract: Four experiments examined judgements of the duration of auditory and visual stimuli. Two used a bisection method, and two used verbal estimation. Auditory/visual differences were found when durations of auditory and visual stimuli were explicitly compared and when durations from both modalities were mixed in partition bisection. Differences in verbal estimation were also found both when people received a single modality and when they received both. In all cases, the auditory stimuli appeared longer than the vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
119
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(135 citation statements)
references
References 20 publications
14
119
1
1
Order By: Relevance
“…Whereas in recent studies cross-modal comparisons between presented time intervals and some stored standard intervals revealed the mixing effect (cf. Penney, et al, 2000;Klapproth, 2004;Wearden, et al, 2006), a similar effect could be shown in this experiment, when two standards were slightly different in duration and were presented within the visual modality.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Whereas in recent studies cross-modal comparisons between presented time intervals and some stored standard intervals revealed the mixing effect (cf. Penney, et al, 2000;Klapproth, 2004;Wearden, et al, 2006), a similar effect could be shown in this experiment, when two standards were slightly different in duration and were presented within the visual modality.…”
Section: Resultssupporting
confidence: 61%
“…Klapproth concluded that "the instruction regarding the putative difference of the standards prevented a mutual shift of the gradients and therefore memory mixing" (Klapproth, 2004, p. 429). The latter result resembled that one recently obtained from Wearden, Todd, and Jones (2006). In their first experiment, a mixedmodality bisection task was used in which the modality of the stimuli was segregated into four distinct blocks.…”
Section: Introductionmentioning
confidence: 51%
“…In time-related tasks, such as duration and empty-interval judgments, differences in precision and accuracy occur between visual and auditory stimuli (see Grondin, 2010, for a review): Auditory signals are perceived as being longer than visual signals of the same duration (e.g., Walker & Scott, 1981;Wearden, Todd, & Jones, 2006), and sensitivity to time is much higher (i.e., lower threshold, or less variability) when intervals are marked by auditory rather than visual signals (Grondin, 2003). It has been hypothesized that the rate of the pacemaker might differ between auditory and visual stimuli in such a way that the internal clock runs faster for auditory than for visual stimuli, and that this "clock speed" difference is the main source of differences in subjective duration across modalities (e.g., Penney et al, 2000;Ulrich, Nitschke, & Rammsayer, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…As a source of this bimodality effect, differences in either clock speed or in the probability of closure of an attentional switch have been used to account for the findings [11,[25][26][27]. In the case of the clock speed account, auditory signals are presumed to drive the pacemaker or oscillatory processes used as the time base for temporal discriminations faster than visual signals, thereby creating proportional differences between the clock readings for physically identical durations.…”
Section: Memory-mixing and Modality Differencesmentioning
confidence: 99%